1998
DOI: 10.1016/s1090-3801(98)90020-9
|View full text |Cite
|
Sign up to set email alerts
|

Controlled‐release oxycodone compared with controlled‐release morphine in the treatment of cancer pain: A randomized, double‐blind, parallel‐group study

Abstract: Controlled-release oral formulations of oxycodone and morphine are both suitable analgesics for moderate to severe pain. They were compared in cancer-pain patients randomized to double-blind treatment with controlled-release oxycodone (n = 48) or controlled-release morphine (n = 52) every 12 h for up to 12 days. Stable analgesia was achieved by 83% of controlled-release oxycodone and 81% of controlled-release morphine patients in 2 days (median). Following titration to stable analgesia, pain intensity (0=none … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(101 citation statements)
references
References 27 publications
4
94
2
1
Order By: Relevance
“…Oxycodone is a semi-synthetic μ-opioid receptor agonist which is widely used in the treatment of both acute and chronic pain [1] The oral bioavailability of oxycodone is over 60% and it is extensively metabolised by duodenal and hepatic cytochrome P450 (CYP) isoenzymes. Only 10% of the oxycodone dose is excreted unchanged in the urine [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Oxycodone is a semi-synthetic μ-opioid receptor agonist which is widely used in the treatment of both acute and chronic pain [1] The oral bioavailability of oxycodone is over 60% and it is extensively metabolised by duodenal and hepatic cytochrome P450 (CYP) isoenzymes. Only 10% of the oxycodone dose is excreted unchanged in the urine [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Nie wpły-wa istotnie na czas pasażu jelitowego w porównaniu z wyraźnie wydłużonym po morfinie już po kilku dniach stosowania. Częstość występowania zaparcia po oksykodonie i morfinie jest podobna, natomiast wymioty i nudności są rzadsze po oksykodonie [58][59][60][61].…”
Section: Rozpoznanie Zaparcia Poopioidowegounclassified
“…It has a biphasic absorption pattern with an initial absorption of about 40% of the drug producing analgesia 1 h after consumption in most patients. The subsequent more controlled absorption accounts for its long duration of effect, which is approximately 12 h. In addition, it is associated with a lower incidence of side effects in cancer patients compared with controlled-release morphine 6 . A recent systematic review by the Cochrane Collaboration showed that singledose oxycodone at doses more than 5 mg was effective for the treatment of acute postoperative pain 7 .…”
Section: Introductionmentioning
confidence: 99%